Clinical and biochemical footprints of inherited metabolic diseases: III. psychiatric presentations - Horvath, Gabriela Ana; Stowe, Robert M.; Ferreira, Carlos R.; Blau, Nenad (Molecular genetics and metabolism, 2020)
Psychiatric symptoms are common manifestations in many inborn errors of metabolism (IEMs), ranging from attention deficit, anxiety and mood and behavioral disorders to psychosis. Furthermore, IEMs represent a significant percentage of all autism cases. We reviewed and updated the list of metabolic disorders known to be associated with various psychiatric manifestations and found more than 100 relevant IEMs. This represents the third of a series of articles attempting to create and maintain a comprehensive list of clinical and metabolic differential diagnoses according to organ system involvement.
Gesehen am 14.05.2020